A review of the research on Chinese typeface design and its user groups - Zhu, Hongyu; Alli, Hassan; Zainal Abidin, Sazrinee (Human Resources Management Academic Research Society (HRMARS), 2024)
With the development of science and Technology, culture, technology and society need typeface design to reflect the cultural heritage and adapt to the development of technology in the digital age. Research on font design and user groups can better meet the needs of users, but also promote the development and innovation of Chinese typeface design. The problem is how to balance the traditional culture and modern technology in Chinese typeface design, and the needs of the user groups is not very detailed survey. Through the questionnaire to collect a large number of user needs and feedback and the use of data analysis to study the development of font design and user needs. It is found that the rapid development of digital media and technology brings new challenges and opportunities to typeface design. Typography on digital platforms is moving in a more diverse direction, with users paying more attention to the appearance and adaptability of typography on different screens. The research direction in the future can further explore the relationship between font design and culture, traditional art. Research should focus on a more comprehensive understanding of user needs, the integration of technology and design, and adapt to the trend of social diversity.